Effect of high mobility group nonhistone proteins HMG-20 (ubiquitin) and HMG-17 on histone deacetylase activity assayed in vitro. - Mezquita, J (1982)
We have used a method previously described by Reeves and Candido (1) to partially release histone deacetylase from cell nuclei together with putative regulators of the enzyme. Histone deacetylase released from testis cell nuclei and its putative regulators were separated by gel filtration in Sepharose 6B. A peak of low molecular weight contains a heat-stable factor that stimulate histone deacetylase in vitro. Many of the properties of the activator coincide with those of the protein HMG-20 (ubiquitin). Ubiquitin isolated from testis cell nuclei stimulated histone deacetylase in vitro. It has been suggested that HMG-17 partially inhibits histone deacetylase in Fried cell nuclei (2). In our system, HMG-17 shows no inhibitory effect on histone deacetylase activity